Universal health coverage and primary care, Thailand - Sumriddetchkajorn, Kanitsorn (Bull World Health Organ, 2019)
Thailand’s policy on universal health coverage (UHC) has made good progress since its inception in 2002. Every Thai citizen is now entitled to essential preventive, curative and palliative health services at all life stages. Like its counterparts elsewhere, however, the policy faces challenges. A predominantly tax-financed system in a nation with a high proportion of people living in poverty will always strive to contain rising costs. Disparities exist among the different health insurance schemes that provide coverage for Thai citizens. National health expenditure is heavily borne by the government, primarily to reduce financial barriers to access for the poor. The population is ageing and the disease profiles of the population are changing alongside the modernization of Thai people’s lifestyles. Thailand is now aiming to enhance and sustain its UHC policy. We examine the merits of different policy options and aim to identify the most promising and feasible way to enhance and sustain UHC. We argue that developing the existing primary care system in Thailand has the greatest potential to provide more self-sustaining, efficient, equitable and effective UHC. Primary care needs to move from its traditional role of providing basic disease-based care, to being the first point of contact in an integrated, coordinated, community-oriented and person-focused care system, for which the national health budget should be prioritized.